Controlling omni-directional Wheels of a MSL RoboCup autonomous mobile robot - Ribeiro, A. Fernando (2004)
Autonomous Mobile Locomotion is of extreme importance in RoboCup robots. Even though in 2050 the robotic team will very likely use legs rather than wheels, at the moment all teams on middle size league use wheels to overcome other problems first. Most teams are using two driving wheels (with one or two cast wheels), four driving wheels and even three driving wheels. The Minho team has been using two driving wheels for the last 5 years (with two caster wheels), but for reaction speed optimization purposes a new approach of three wheels is being developed. This paper deals with the description of such platform, it describes the advantages and also the type of control used.